PALM KERNEL SHELL ASH: THE EFFECT OF WEIGHT AND STIRRING DURATION ON WASTE PALM COOKING OIL QUALITY - Lidya Novita; Yuliana Arsil; Iswadi Idris (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
This study aims to investigate the effect of variations Palm Kernel Shell Ash (PKSA) in weight and stirring duration on the quality of waste palm cooking oil (WPCO). PKSA is waste from the use of Palm Kernel Shell (PKS) as fuel in palm oil factories. The method used in this study is a laboratory experiment with variations in the weight of PKSA and variations in stirring duration to improve WPCO quality. PKSA was characterized using XRF, FTIR, and XRD. The parameters of WPCO analyzed were color, water content, and free fatty acid (FFA). The standard used for comparison was the SNI for palm cooking oil 7709-2019. The results showed that the treatment category of S3, where PKSA was 20 g and stirring duration was 90 min, decreased the parameter value of WPCO according to SNI requirements. The improved quality of WPCO can be used for various purposes, including biodiesel, fertilizer and poultry feed.